Clinical Characteristics and Outcome of Spontaneous Intracerebral Hemorrhage (Journal of Nobel Medical College, 2024)
Background: Stroke is the second leading cause of death and disability globally. Intracerebral hemorrhage represents a prominent subtype comprising 10-20% of all strokes and posing substantial challenges, particularly in low-income countries. This study aims to unravel the clinical profile and outcomes of spontaneous ICH patients at our institute.Materials and Methods: This is a prospective observational study conducted at the department of Neurosurgery Nobel Medical College Teaching Hospital, Biratnagar, Nepal over a period of one and half years.Results: In the Present study, a total of 285 populations were studied, where there was male preponderance with the mean age of 57.9 years. Commonest clinical manifestation was sudden onset headache (75.1%) followed by decreased level of consciousness.  Hypertension was the commonest cause of ICH. Basal ganglia were the primary location of bleed. The statistical analysis revealed a significant difference in the mean clot volume between survivors and non-survivors. There was a strong association between ventricular extension of hematoma and outcome. Surgical hematoma evacuation was performed in 30.9% of cases. Favorable outcomes, defined by a modified Rankin Scale score of 0-3, were achieved in 58.9% of participants.Conclusion: Age, sudden onset headache, and hypertension predict mortality in primary intracerebral hemorrhage (ICH), particularly with advanced age linked to poorer outcomes. A Glasgow Coma Score less than eight increases mortality risk, while clot volume and intraventricular extension play crucial roles in ICH outcome.